A STUDY OF UNDERGRADUATE STUDENTS' ATTITUDE, MOTIVATION AND DIFFICULTIES ON THE USE OF MOBILE VOCABULARY LEARNING, ASSUMPTION UNIVERSITY - PAN, LI; DEOCAMPO, MARILYN FERNANDEZ (Scholar: Human Sciences, 2022)
This study investigates the undergraduates’ attitudes, motivation, and learning difficulties in using mobile devices via vocabulary learning. The participants of this research are full-time undergraduates studying at Suvarnabhumi Campus, Assumption University (AU). This study used a mixed-method and focused on the exploratory design. For the questionnaire survey, 200 participants were selected using convenience sampling from the population. For the semi-structured interview, 15 participants were selected by using simple random sampling. The findings indicated that although 100% of the participants have mobile devices, some still used a traditional method, and the most popular vocabulary applications are Duolingo and BaiCiZhan. Also, students’ attitudes toward using mobile devices were HIGH as the overall mean score (M) = 3.68. The indication is that students have positive attitudes towards using mobile devices at Assumption University. Moreover, students’ motivation towards using mobile devices in AU is also HIGH. The overall mean score (M) = 3.68. As suggested, AU students are highly motivated to use mobile devices in teaching and learning. Lastly, students’ difficulties with using mobile devices are MODERATE, with the overall mean score (M) = 2.76. This can be interpreted those students were having moderate difficulties with using mobile devices. Based on the findings, a few pedagogical implications were discussed, and recommendations for students and teachers were suggested to foster mobile vocabulary learning in the English language classroom.